Can strong capital regulation prevent risk-taking from deposit insurance?. Issue 12 (13th August 2021) - Bartholdy, Jan; Justesen, Lene Gilje
Abstract : Can strong capital regulation prevent risk-taking from deposit insurance? Denmark offers a unique setting providing solid identification for testing risk incentives from deposit insurance under strong capital regulation. The Danish system is a universal system without strong risk exposure regulation. Commercial banks and savings banks have different ownership structures but are subject to the same set of regulations, but savings banks have no incentive to increase risk after the implementation of a deposit insurance scheme. We show that commercial banks did not increase their risk at the introduction of deposit insurance compared to savings banks. We attribute this to strong capital requirements and a firm closure policy. The results also hold for large commercial banks, indicating that the systemic risk did not increase either. Finally, there is no evidence that commercial banks increase their risk by allowing their customers to increase their leverage (risk) compared with customers in savings banks.